2021
DOI: 10.3389/fnsys.2021.611507
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Inhibitory Control Processes Using Individualized High Definition Theta Transcranial Alternating Current Stimulation (HD θ-tACS) of the Anterior Cingulate and Medial Prefrontal Cortex

Abstract: Increased frontal midline theta activity generated by the anterior cingulate cortex (ACC) is induced by conflict processing in the medial frontal cortex (MFC). There is evidence that theta band transcranial alternating current stimulation (θ-tACS) modulates ACC function and alters inhibitory control performance during neuromodulation. Multi-electric (256 electrodes) high definition θ-tACS (HD θ-tACS) using computational modeling based on individual MRI allows precise neuromodulation targeting of the ACC via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 80 publications
(148 reference statements)
1
14
0
Order By: Relevance
“…In younger adults, PFC theta tACS also shows promise for improving sustained attention, related to strengthened alpha (8–12 Hz) connectivity in the dorsal attention network ( Rostami et al, 2021 ). Improved inhibitory control has also been observed following PFC theta tACS, however, only when the theta frequency matches an individual’s peak frequency ( Klírová et al, 2021 ), similar to results from working memory studies ( Reinhart and Nguyen, 2019 ). The recent successes of tACS, when optimized to affect brain networks, set the groundwork for developing therapeutics for individuals with clinical diagnoses that implicate cognitive control.…”
Section: Introductionsupporting
confidence: 60%
“…In younger adults, PFC theta tACS also shows promise for improving sustained attention, related to strengthened alpha (8–12 Hz) connectivity in the dorsal attention network ( Rostami et al, 2021 ). Improved inhibitory control has also been observed following PFC theta tACS, however, only when the theta frequency matches an individual’s peak frequency ( Klírová et al, 2021 ), similar to results from working memory studies ( Reinhart and Nguyen, 2019 ). The recent successes of tACS, when optimized to affect brain networks, set the groundwork for developing therapeutics for individuals with clinical diagnoses that implicate cognitive control.…”
Section: Introductionsupporting
confidence: 60%
“…The third limitation is the lack of a control frequency. Similar to previous tACS studies [ 43 46 ], we compared stimulation effects between a frequency of interest and sham condition, without involving any control frequencies to rule out confounding effects brought by the frequency factor [ 47 48 ]. Future study could provide more convincing evidence of frequency-specific effects by introducing a control frequency condition.…”
Section: Discussionmentioning
confidence: 99%
“…Brain stimulation studies also support the role of pre/frontal theta activity in response inhibition (Klírová et al, 2021). Obeso et al (2017) showed that continuous theta burst magnetic stimulation over pre-supplementary motor cortex facilitated motor inhibition in healthy participants.…”
mentioning
confidence: 88%